Being a good financial auditor. Conceptions of responsibilities among accountancy students - Gjalt de Graaf (Pensoft, 2021)
Auditors serve several masters. They have a clear obligation towards society, which expects them to be honest in checking the books of what are sometimes influential and wealthy institutions. At the same time, auditors are hired and paid by their clients, the companies they audit, who may have clear expectations in return. Sometimes the different obligations auditors have, or perceive to have, can conflict. We focus here on accountancy students who already work part-time at accountancy firms and who will shape the future of accounting. Our main research question is: What different conceptions of auditor responsibilities exist among accountancy students? We used Q-methodology, a mixed-methods approach, to identify and describe the views accountancy students have on what are the responsibilities of an auditor. We found four conceptions of auditor responsibilities among accountancy students in the Netherlands that are distinct in how they deal with conflicts between professional behaviour, integrity, objectivity, and professional competence.